Linking Conformation Change to Hemoglobin Activation Via Chain-Selective Time-resolved Resonance Raman Spectroscopy on Protoheme/Mesoheme Hybrids - Balakrishnan, Gurusamy (2009)
Time-resolved Resonance Raman spectra are reported for Hb tetramers, in which the αand β chains are selectively substituted with mesoheme. The Soret absorbtion band shift in meso- relative to proto-heme permits chain-selective excitation of heme RR spectra. The evolution of these spectra following HbCO photolysis show that geminate recombination rates and yields are the same for the two chains, consistent with recent results on (15)N-heme isotopomer hybrids. The spectra also reveal systematic shifts in the deoxy-heme ν(4) and ν(Fe-His)) RR bands, which are anti-correlated. These shifts are resolved for the successive intermediates in the protein structure, which have previously been determined from time-resolved UVRR spectra. Both chains show Fe-His bond compression in the immediate photoproduct, which relaxes during the formation of the first intermediate, R(deoxy) (0.07 μs), in which the proximal F-helix is proposed to move away from the heme. Subsequently, the Fe-His bond weakens, more so for the α than the β chains. The weakening is gradual for the β chains, but abrupt for the α chains, coinciding with completion of the R-T quaternary transition, at 20μs. Since the transition from fast- to slow-rebinding Hb also occurs at 20μs, the drop in the α chain ν(Fe-His) supports the localization of ligation restraint to tension in the Fe-His bond, at least in the α-chains. The mechanism is more complex in the β chains.